The Science Behind Continuous Glucose Monitoring Wearables: A Deep Dive for Digital Health Professionals - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Introduction: The Revolution of Real-Time Metabolic Data Continuous Glucose Monitoring (CGM) wearables have moved beyond diabetes management to become a...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Wearable Technology